Fabrication and simulation of V-shaped Ag nanorods as high-performance SERS substrates. Issue 40 (4th October 2018) - Li, Jianghao; Fan, Yihang; Xue, Xiaotian; Ma, Lingwei; Zou, Sumeng; Fei, Zhu; Xie, Zheng; Zhang, Zhengjun
Abstract : V-shaped AgNRs have a higher SERS sensitivity than straight AgNRs and their resonance wavelengths can be tuned linearly. Abstract : Bending straight Ag nanorods (AgNRs) into V-shaped structures can generate a higher surface-enhanced Raman scattering (SERS) performance. Numerical simulations showed that V-shaped AgNRs with a total length between 300 nm and 800 nm were more sensitive than equal-length straight AgNRs under a 785 nm laser in most cases. It was found that at a laser wavelength between 500 nm and 1000 nm, the Raman enhancement factor (EF) of a V-shaped AgNR's 3rd plasmon mode was not only optimal among the other major plasmon modes, but also outperformed the plasmon modes of straight AgNRs. Besides, a linear relationship between the resonance wavelength of the V-shaped AgNR's 3rd mode and its length was observed both numerically and experimentally, which was beneficial for the optimization of SERS substrates. Under 785 nm laser excitation, V-shaped AgNR substrates with a single arm length between 330 nm and 340 nm possessed the highest SERS efficiency. This work took AgNR array substrates one step closer to practical applications.